Schemes For Enhancing Climate Change Resilience Among Rice Farmers For Food Security In Ebonyi State, Nigeria - Egbe, Egbe; O, Banjamin; Ernest Ituma, Ogba; Agnes, Esheya; Onwe Kelvin A, U.,; Chukwudi Goodluck, Uguru (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study determined schemes for enhancing climate change resilience among rice farmers for food security in Ebonyi State. Three specific purposes guided the study. The study was a survey research design and used questionnaire to elicit information from 162 respondents, made up of 108 registered rice farmers and 54 extension agents. Data collected through the questionnaire were analyzed using mean and standard deviation to answer the research questions, while t-test was used to test the hypotheses. The study identified seven schemes from government, seven schemes from agricultural institutions and six from farm practices for farmers to adopt to manage climate change. It implies that if government could packaged the identified schemes into extension training programme, farmers could be resilient in the face of climate change. It was then recommended that extension agents should train and encourages farmers to adopt the schemes.